2016
DOI: 10.1016/j.jcf.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A novel culture medium for isolation of rapidly-growing mycobacteria from the sputum of patients with cystic fibrosis

Abstract: RGM medium offers a simple and effective culture method for the isolation of rapidly-growing mycobacteria from sputum samples from patients with CF without decontamination of samples. RGM medium allows for the systematic screening of all sputum samples routinely referred for culture from patients with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 27 publications
(25 reference statements)
3
35
0
Order By: Relevance
“…44347) for the isolation of mycobacteria from 502 sputum samples. Mycobacteria were detected in 54 samples using RGM medium and in only 17 samples using Cepacia selective agar (P Յ 0.0001) (18). As media for the isolation of B. cepacia have been recommended for the isolation of mycobacteria, this prompted us to examine different commercial brands of such media, to compare their abilities to support the growth of rapidly growing mycobacteria and their selectivity against other flora associated with CF sputum samples.…”
Section: Discussionmentioning
confidence: 99%
“…44347) for the isolation of mycobacteria from 502 sputum samples. Mycobacteria were detected in 54 samples using RGM medium and in only 17 samples using Cepacia selective agar (P Յ 0.0001) (18). As media for the isolation of B. cepacia have been recommended for the isolation of mycobacteria, this prompted us to examine different commercial brands of such media, to compare their abilities to support the growth of rapidly growing mycobacteria and their selectivity against other flora associated with CF sputum samples.…”
Section: Discussionmentioning
confidence: 99%
“…In the first published evaluation of the use of RGM medium, Preece et al demonstrated performance superior to the use of BCSA for recovery of mycobacteria (11). The study examined 502 consecutive sputum samples from patients with CF in the United Kingdom and reported that 54 isolates of NTM were recovered on RGM medium versus 17 recovered on BCSA (P Յ 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all NTM will grow on BCSA and overgrowth, particularly by fungi and Gram-negative bacteria, remains a problem (10). Preece et al (11) recently described a new selective agar, RGM medium, to target rapidly growing species of mycobacteria, which represent the dominant species in many geographical areas (3,4,12). The sensitivity of RGM medium proved to be clearly superior to that of BCSA when evaluated with 502 sputum samples from patients with CF.…”
mentioning
confidence: 99%
“…We also found that isolates were obtained from a gastric source with MABSC negative sputa. MABSC were therefore identified for the first time from a gastric sample in these patients, despite rigorous and extended previous sputum based surveillance in a tertiary laboratory, with a specialised interest in MABSC culture methodology16.…”
Section: Discussionmentioning
confidence: 99%